Effect of electrode and electric current on peat water treatment with continuous electrocoagulation process. (2022) - Amri, Idral; Herman, Syamsu; Fadhlah Ramadan, Albi; Hamzah, Nirwana
Abstract: Peat water is surface water that inundates an area, formed from a pile of organic material for a long time. Peat water can skin irritation and metabolic disorders. The purpose of this study was to determine the application of the electrocoagulation method to neutralize pH and reduce levels of TSS and Fe in peat water and also to determine the effect of changes in electrode distancing and electric current on decreasing TSS and Fe levels and neutralizing the pH of peat water. The parameters tested include pH, TSS (Total Suspended Solid), and Fe content. The electrocoagulation process used electric current which flows in the direction through the electrodes. Electrocoagulation pipe was installed with electric cable that connected to the power supply with variation of current (1.0; 1.4; and 1. 8 A) and electrode distancing variations (0.5; 0.75; 1 in.). The results of this study show the optimum conditions obtained at 1.8 Ampere and 0.75-inch electrode distance with an increase in pH from 3.5 to 6.8, removing TSS from 128 to 36 mg / L, a decreasing Fe of 78.9% from 2.405 mg/L to 0.506 mg/L.